Live and inactivated Piscirickettsia salmonis activated nutritional immunity in Atlantic salmon (Salmo salar) - Martínez, Danixa; Oyarzún-Salazar, Ricardo; Quilapi, Ana María; Coronado, José; Enriquez, Ricardo; Vargas-Lagos, Carolina; Oliver, Cristian; Santibañez, Natacha; Godoy, Marcos; Muñoz, José Luis; Vargas-Chacoff, Luis; Romero, Alex (Frontiers in Immunology, 2023)
Nutritional immunity regulates the homeostasis of micronutrients such as iron, manganese, and zinc at the systemic and cellular levels, preventing the invading microorganisms from gaining access and thereby limiting their growth. Therefore, the objective of this study was to evaluate the activation of nutritional immunity in specimens of Atlantic salmon (Salmo salar) that are intraperitoneally stimulated with both live and inactivated Piscirickettsia salmonis. The study used liver tissue and blood/plasma samples on days 3, 7, and 14 post-injections (dpi) for the analysis. Genetic material (DNA) of P. salmonis was detected in the liver tissue of fish stimulated with both live and inactivated P. salmonis at 14 dpi. Additionally, the hematocrit percentage decreased at 3 and 7 dpi in fish stimulated with live P. salmonis, unchanged in fish challenged with inactivated P. salmonis. On the other hand, plasma iron content decreased during the experimental course in fish stimulated with both live and inactivated P. salmonis, although this decrease was statistically significant only at 3 dpi. Regarding the immune-nutritional markers such as tfr1, dmt1, and ireg1 were modulated in the two experimental conditions, compared to zip8, ft-h, and hamp, which were down-regulated in fish stimulated with live and inactivated P. salmonis during the course. Experimental. Finally, the intracellular iron content in the liver increased at 7 and 14 dpi in fish stimulated with live and inactivated P. salmonis, while the zinc content decreased at 14 dpi under both experimental conditions. However, stimulation with live and inactivated P. salmonis did not alter the manganese content in the fish. The results suggest that nutritional immunity does not distinguish between live and inactivated P. salmonis and elicits a similar immune response. Probably, this immune mechanism would be self-activated with the detection of PAMPs, instead of a sequestration and/or competition of micronutrients by the living microorganism.